LITERASI EKONOMI SYARIAH DAN TEMAN SEBAYA TERHADAP MINAT MENABUNG DI PERBANKAN SYARIAH - Noni Rozaini; Rizki Husnul Amelia; Ina Namora Putri Siregar; Mica Siar Meiriza (Niagawan, 2022)
This study aims to determine how much the influence of sharia economic literacy and peers on student savings interest in Islamic banking (study on students of the 2014 batch of Economic Education Study Program at the State University of Medan. The population in this study were all students of 2014 Economic Education Study Program totaling 126 students with 96 students as research samples.The sampling technique used is simple random sampling. Data collection techniques are carried out by means of tests and questionnaires. Test the validity of the questionnaire using the Pearson product moment formula, and its reliability is calculated using Cronbach Alpha. The research data analysis technique is multiple linear regression to test the research hypothesis using t test and F test. The results of multiple regression analysis obtained equation Y = 31,058 - 0,020X1 + 0,320X2 + e. Furthermore, the coefficient of determination (R2) is 0.362 which means that it is equal to 36.2%, the variables X1 and X2 can explain the interest in saving students (Y) and the scales of 63.8% are explained by other variables not examined in this study. Based on the t test, it was found that each variable X1 did not have a positive and significant effect on students' savings interest (Y) in Islamic banking with a tcount <ttable (0.675 <1.666) and there was a positive and significant influence between X2 variables on student savings ( Y) in Islamic banking with a value of t> t table (7.259> 1.666). While the F test found that there is a positive and significant influence between Islamic economic literacy (X1) and peers (X2) on the interest in saving students (Y) in Islamic banking with a value of Fcount> Ftable (26.739> 3.09) and significance value ( 0,000 <0,05).